Haemoglobin Gene Repertoire in Teleost and Cichlid Fishes Shaped by Gene Duplications and Genome Rearrangements - Omelchenko, Dmytro; Bitja-Nyom, Arnold Roger; Matschiner, Michael; Malinsky, Milan; Indermaur, Adrian; Salzburger, Walter; Bartoš, Oldřich; Musilova, Zuzana (Molecular ecology, 2024)
Haemoglobin is a key molecule for oxygen transport in vertebrates. It exhibits remarkable gene diversity in teleost fishes, reflecting adaptation to various aquatic environments. In this study, we present the dynamic evolution of haemoglobin subunit genes based on a comparison of high-quality genome assemblies of 24 vertebrate species, including 17 teleosts (of which six are cichlids). Our findings indicate that teleost genomes contain a range of haemoglobin genes, from as few as five in fugu to as many as 43 in salmon, with the latter being the largest repertoire found in vertebrates. We find evidence that the teleost ancestor had at least four Hbα and three or four Hbβ subunit genes, and that the current gene diversity emerged during teleost radiation, driven primarily by (tandem) gene duplications, genome compaction, and rearrangement dynamics. We provide insights into the genomic organisation of haemoglobin clusters in different teleost species. We further show that the evolution of paralogous rhbdf1 genes flanking both teleost clusters (LA and MN) supports the hypothesis for the origin of the LA cluster by rearrangement within teleosts, rather than by the teleost specific whole-genome duplication. We specifically focus on cichlid fishes, where adaptation to low oxygen environment plays role in species diversification. Our analysis of six cichlid genomes, including Pungu maclareni from the Barombi Mbo crater lake, for which we sequenced a representative genome, reveals 18-32 copies of the Hb genes, and elevated rates of non-synonymous substitutions compared to other teleosts. Overall, this work facilitates a deeper understanding of how haemoglobin genes contribute to the adaptive potential of teleosts.
Keywords: molekulární evoluce; evolution; genová přestavba; duplikace genu; cichlids; synteny; Evolution, Molecular; Hemoglobins; Cichlids; Gene Rearrangement; Genome; cichlidy; Gene Duplication; duplication; haemoglobin; teleosts; zvířata; fylogeneze; genom; hemoglobiny; Fishes; ryby; Phylogeny; Animals